Plasminogen activator inhibitor 1 is associated with high-grade serous ovarian cancer metastasis and is reduced in patients who have received neoadjuvant chemotherapy - Kelly, Tanya E.; Spillane, Cathy L.; Ward, Mark P.; Hokamp, Karsten; Huang, Yanmei; Tewari, Prerna; Martin, Cara M.; Norris, Lucy A.; Mohamed, Bashir M.; Bates, Mark; Brooks, Robert; Selemidis, Stavros; et al. (Frontiers in Cell and Developmental Biology, 2023)
High-grade serous ovarian cancer (HGSOC) is the most prevalent and deadliest subtype of epithelial ovarian cancer (EOC), killing over 140,000 people annually. Morbidity and mortality are compounded by a lack of screening methods, and recurrence is common. Plasminogen-activator-inhibitor 1 (PAI-1, the protein product of SERPIN E1) is involved in hemostasis, extracellular matrix (ECM) remodeling, and tumor cell migration and invasion. Overexpression is associated with poor prognosis in EOC. Platelets significantly increase PAI-1 in cancer cells in vitro, and may contribute to the hematogenous metastasis of circulating tumor cells (CTCs). CTCs are viable tumor cells that intravasate and travel through the circulation -often aided by platelets -with the potential to form secondary metastases. Here, we provide evidence that PAI-1 is central to the platelet-cancer cell interactome, and plays a role in the metastatic cascade. SK-OV-3 cells where PAI-1 had been silenced, treated with healthy donor platelets, and treated with platelet-conditioned medium were used as an in vitro model of metastatic EOC. Gene expression analysis was performed using RNA-Seq data from untreated cells and cells treated with PAI-1 siRNA or negative control, each with and without platelets. Four cohorts of banked patient plasma samples (n = 239) were assayed for PAI-1 by ELISA. Treatment-naïve (TN) whole blood (WB) samples were evaluated for CTCs in conjunction with PAI-1 evaluation in matched plasma.Significant phenotypic changes occurring when PAI-1 was silenced and when platelets were added to cells were reflected by RNA-seq data, with PAI-1 observed to be central to molecular mechanisms of EOC metastasis. Increased proliferation was observed in cells treated with platelets.Plasma PAI-1 significantly correlated with advanced disease in a TN cohort, and was significantly reduced in a neoadjuvant chemotherapy (NACT) cohort. PAI-1 demonstrated a trend towards significance in overall survival (OS) in the late-stage TN cohort, and correlation between PAI-1 and neutrophils in this cohort was significant. 72.7% (16/22 ) of TN patients with plasma PAI-1 levels higher NER